Effects of Macroeconomic Policies on Rural Nonfarm Enterprises - Aida R. Librero (Philippine Institute for Development Studies (PIDS), 1994)
With the excessive labor supply and the persistence of urban-rural migration, the development of nonfarm enterprises is imperative from the government. This paper develops an analytical framework to determine the impact of macroeconomic policies on rural nonfarm enterprises (RNEs). It also analyzes the trends in RNEs growth, the changes in the government policies towards sector and the markets for its output.
Keywords: 330; food sector; investment incentive system; tax effort; rural nonfarm enterprise; employment opportunities; coconut oil; sugar products; fertilizer industry; trade policies; tax exemption